2014
DOI: 10.1080/14735903.2014.986363
|View full text |Cite
|
Sign up to set email alerts
|

Conserving landraces and improving livelihoods: how to assess the success of on-farm conservation projects?

Abstract: Smallholder farmers who grow diverse landraces in centres of crop diversity contribute to sustaining the capacity of agricultural and food systems to adapt to change by maintaining crop evolution in their fields today, thus enabling humanity to continue to have the broad genetic variation needed to adapt crops to changes tomorrow. Given this fact, the last 20 years have witnessed an ever-growing interest in on-farm conservation of crop infra-specific diversity. While numerous projects to support it have been, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 72 publications
0
59
0
3
Order By: Relevance
“…In the last 20 years, many projects to support OFC have been implemented worldwide. There has been very little systematic assessment, however, of the extent to which OFC projects have actually made a difference beyond what de facto conservation is already delivering (Bellon, Gotor, & Caracciolo, 2015;Bellon & van Etten, 2014). For example, a recent and extensive review (Jarvis, Hodgkin, Sthapit, Fadda, & LopezNoriega, 2011) identified 59 different types of interventions for supporting OFC worldwide, but there is little evidence that they actually made a difference.…”
Section: Introductionmentioning
confidence: 94%
“…In the last 20 years, many projects to support OFC have been implemented worldwide. There has been very little systematic assessment, however, of the extent to which OFC projects have actually made a difference beyond what de facto conservation is already delivering (Bellon, Gotor, & Caracciolo, 2015;Bellon & van Etten, 2014). For example, a recent and extensive review (Jarvis, Hodgkin, Sthapit, Fadda, & LopezNoriega, 2011) identified 59 different types of interventions for supporting OFC worldwide, but there is little evidence that they actually made a difference.…”
Section: Introductionmentioning
confidence: 94%
“…The project assessment was developed using the theoretical framework developed by Bellon et al (2015a), that provides a series of linked hypotheses needed to assess the success of a in situ/onfarm conservation program. One of the most common objective faced by institutions and scholars that implement development programs aiming to promote the sustainable use of agricultural diversity in rural settings is the identification of the intervention pathways needed to reach a significant and tangible impact.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 represents the sustainable pathway of an effective in situ, on-farm conservation project. According this framework, the following four hypotheses should be tested in order to assess the success of in situ, on-farm conservation project (Bellon et al 2015a): a) Participation in project interventions leads farmers to apply options provided by the interventions; b) The application of these options leads to farmers maintaining higher levels of wild fruit diversity than would have been possible without the interventions; c) Farmers with higher levels of diversity obtain additional benefits from this diversity; d) The higher levels of fruit diversity linked with the application of these options are associated with higher levels of genetic diversity than would have occurred otherwise.…”
Section: Program Description and Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations